2009
DOI: 10.1055/s-0029-1244805
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Near-infrared Fluorescence Imaging in Perforator Flap Reconstruction: Current Research and Early Clinical Experience

Abstract: Despite recent advances in perforator flap reconstruction, there can be significant variability in vessel size and location. Although pre-operative evaluation may provide valuable information, real-time intraoperative methods have the potential to provide the greatest benefit. Our laboratory has developed the Fluorescence-Assisted Resection and Exploration (FLARE™) near-infrared (NIR) fluorescence imaging system for visualizing, intraoperatively, details of the underlying vasculature. The FLARE™ system uses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 24 publications
(51 reference statements)
0
86
0
Order By: Relevance
“…Indocyanine green is a fluorescing reagent used for intraoperative visualization of vascular patency in neuroangiography [36], cardiovascular surgery [37], and solid organ transplantation [38], and plastic and reconstructive surgery [39]. A tricarbocyanine dye that appears dark green in natural light, indocyanine green absorbs light in the near-infrared range and emits maximum fluorescence at a wavelength of 840 nm when bound to plasma proteins.…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…Indocyanine green is a fluorescing reagent used for intraoperative visualization of vascular patency in neuroangiography [36], cardiovascular surgery [37], and solid organ transplantation [38], and plastic and reconstructive surgery [39]. A tricarbocyanine dye that appears dark green in natural light, indocyanine green absorbs light in the near-infrared range and emits maximum fluorescence at a wavelength of 840 nm when bound to plasma proteins.…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…ICG has a short lifetime in the blood (2-4 min plasma half-life) and slow plasma clearance rate once bound to the plasma proteins [15]. Earlier, ICG was used to assess cardiac and liver functions and lately, its applications have been diversified to visualize bile ducts, vascular networks, and demarcation of liver segments [16][17][18][19]. Although various NIR fluorescent contrast agents have been developed and tested in preclinical studies only ICG is approved by the FDA for fluorescence imaging [20].…”
Section: Fluorescent Dyes and Probesmentioning
confidence: 99%
“…1 We recently reported that affected subcutaneous adipose tissue in patients with FIL contains mutant cells with somatic gain-offunction mutations in PIK3CA. 2 The purpose of this study was to determine whether other affected tissues in FIL also contain mutant cells.…”
Section: Facial Infiltrating Lipomatosis Containsmentioning
confidence: 99%